Molecular design driving tetraporphyrin self-assembly on graphite: a joint STM, electrochemical and computational study. Issue 28 (4th July 2016) - El Garah, M.; Santana Bonilla, A.; Ciesielski, A.; Gualandi, A.; Mengozzi, L.; Fiorani, A.; Iurlo, M.; Marcaccio, M.; Gutierrez, R.; Rapino, S.; Calvaresi, M.; Zerbetto, F.; et al.
Abstract : Supramolecular engineering of porphyrin-based 2D architectures via non-covalent interactions. Abstract : Tuning the intermolecular interactions among suitably designed molecules forming highly ordered self-assembled monolayers is a viable approach to control their organization at the supramolecular level. Such a tuning is particularly important when applied to sophisticated molecules combining functional units which possess specific electronic properties, such as electron/energy transfer, in order to develop multifunctional systems. Here we have synthesized two tetraferrocene-porphyrin derivatives that by design can selectively self-assemble at the graphite/liquid interface into either face-on or edge-on monolayer-thick architectures. The former supramolecular arrangement consists of two-dimensional planar networks based on hydrogen bonding among adjacent molecules whereas the latter relies on columnar assembly generated through intermolecular van der Waals interactions. Scanning Tunneling Microscopy (STM) at the solid–liquid interface has been corroborated by cyclic voltammetry measurements and assessed by theoretical calculations to gain multiscale insight into the arrangement of the molecule with respect to the basal plane of the surface. The STM analysis allowed the visualization of these assemblies with a sub-nanometer resolution, and cyclic voltammetry measurements provided direct evidence of the interactions of porphyrin and ferrocene with the graphite surface and offered also insight into the dynamics within the face-on and edge-on assemblies. The experimental findings were supported by theoretical calculations to shed light on the electronic and other physical properties of both assemblies. The capability to engineer the functional nanopatterns through self-assembly of porphyrins containing ferrocene units is a key step toward the bottom-up construction of multifunctional molecular nanostructures and nanodevices.